(untitled) (Medico Legal Update, 2020)
Recently Cabinet has passed the proposed Medical Termination of Pregnancy (Amendment) Bill, 2020. In current bill certain changes has been made regarding the upper limit of gestational age for termination of pregnancy under MTP Act, 1971. Through this paper researcher will discuss about the drawback of the MTP (Amendment) Bill, 2020 in terms of gestational age with the help of the various judicial pro-announcement.